#OrthoTwitter: social media as an educational tool. (5th September 2020) - Sahu, Muhammad Arham; Goolam-Mahomed, Zahrah; Fleming, Simon; Ahmed, Usman
Abstract : Aims: The increased use of social media creates opportunity for new, effective methods of delivering medical and clinical education. Twitter is a popular social media platform where users can post frequent updates and create threads containing related content using hashtags. This study aims to investigate and analyse the type of content relating to orthopaedic surgery that is being posted on the platform of Twitter. Methods: A retrospective search was performed for tweets containing the words 'orthopaedic surgery' or 'orthopedic surgery' or the use of the hashtag '#OrthoTwitter' between November 2018 to November 2019. A total of 5243 tweets were included. Results: Tweets containing 'orthopaedic surgery' or 'orthopedic surgery' most frequently contained promotional or marketing content (30% promotional, 21% marketing), and private organisations were the category of author to which the greatest number of tweets belonged (30%). Tweets containing educational or research content were the least common among all tweets containing 'orthopaedic surgery' or 'orthopedic surgery' (11%). In contrast, of the tweets containing the hashtag '#OrthoTwitter', 44% contained educational or research content, 15% contained promotional content and no tweets containing marketing content. Furthermore, 87% of all tweets using the hashtag '#OrthoTwitter' were from orthopaedic surgeons, and the least number of tweets were from private organisations (2%). Conclusion: Twitter is a widely used social media platform regarding orthopaedic surgery. We propose that the hashtag '#OrthoTwitter' can be used to create an online community of orthopaedic surgeons where members can assist one another through sharing reliable and educational content.